Pengaruh Kombinasi Stimulasi Pijat bayi dan Esensial Oil Lavender Terhadap Motorik Kasar dan Motorik Halus Pada Bayi Usia 3-12 Bulan di Kota Bengkulu - Rina, Rina; Wahyuni , Elly; Rositarini, Mike (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2024)
Background: The growth and development period of infants needs special attention because the process is very fast. There are still toddlers who experience gross motor and fine motor disorders. World Health Organization (WHO) 2016 globally states that around 20-40% of infants aged 0-2 years experience problems with delays in the development process, 5-25% of toddlers who experience gross motor and fine motor disorders. The impact of delays in infant gross motor development causes a decrease in creativity in the adaptation period while the impact of delays in fine motor development causes obstacles in the child's learning process. Efforts that can be made in optimizing the growth and development of fine motor and gross motor in infants in addition to nutrition provided by the mother and one of the other ways needs stimulation. The combination of stimulation of baby massage and lavender essential oil is one of the stimulations to improve gross motor and fine motor in infants aged 3-12 months. Objective: Proving the effect of a combination of baby massage stimulation and lavender essential oil on improving gross motor and fine motor in infants aged 3-12 months. Methods: Pre-experimental quantitative research design with one group pretest-postest design. Sample 40 infants aged 3-12 months. Analysis used to assess the effect on the improvement of gross motor and fine motor in 2 PMB using t test. Results: Hypothesis testing in this study using the Wilcoxon test. Obtained a probability value (p value) of (p value) 0.02 or < 0.05, which means that there is a combined effect of baby massage stimulation and lavender essential oil on improving gross motor and fine motor in infants aged 3-12 months. The intervention was given for 4 weeks, twice a week the intervention was given a combination of baby massage and lavender essential oil, then an evaluation was carried out using the Pre-Developmental Screening Questionnaire (KPSP), consisting of 10 assessment items, starting from gross motor, fine motor, socialization and independence assessments. as well as speech and language skills. Conclusion: The combination of baby massage stimulation and lavender essential oil has an effect on improving gross motor and fine motor in infants aged 3-12 months. Suggestion: parents who have babies are expected to routinely provide baby massage stimulation.